The Effect Of Current Ratio (Cr), Debt To Total Asset Ratio (Dar) And Total Asset Turnover (Tato) On Profit Growth In PT. Ultra jaya milk industry, Tbk for the period 2012-2021 - ida yusnita (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine: 1) To determine the effect of Current Ratio (CR) on Profit Growth at PT.Ultrajaya Milk Industry,Tbk period 2012-2021.2).To determine the effect of Debt To Asset Ratio (DAR), to Profit Growth at PT.Ultrajaya Milk Industry, Tbk period 2012-2021. 3) To determine the effect of Total Asset Turnover (TATO) on profit growth at PT. Ultrajaya Milk Industry, Tbk for the period 2012-2021. 4) To determine the effect of Current Ratio (CR), Debt To Asset Ratio (DAR), Total Asset Turnover (TATO) on profit growth at PT. Ultrajaya Milk Industry, Tbk period 2012-2021.5) To determine the magnitude of the influence of Current Ratio (CR), Debt To Asset Ratio (DAR), Total Asset Turnover (TATO) to profit growth at PT. Ultrajaya Milk Industry,Tbk period 2012-2021.The analytical tool used in this research is multiple linear regression analysis which is logged with the help of statistical software version 20. The source of the data is the financial report data on the IDX website (www.idx.co.id), www. finance.yahoo.com and bps.go.id.Based on the results of the study indicate that: Current Ratio (CR) has an effect but is not significant on profit growth (-1.064 <2.44691 and a significant value of 0.365 <0.05. Debt To Total Asset Ratio (DAR) has an effect but is not significant on profit growth ( -0.885 < 2.44691 and a significant value of 0.441 < 0.05. Total Asset Turnover (TATO) has an effect but is not significant on profit growth (-0.172 < 2.44691) and a significant value -0.172 <0.05. Can be explained by other variables outside the research variables.